Pengenalan Game Edukasi Flora dan Fauna untuk Siswa SD Inpres 4 Arborek Raja Ampat - Tella, Fitriyani; Jundullah, Muhammad; Murni; Nurdjan, Nirwana; Hasa, Muh. Fadli; Ghiraldy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Education in remote areas often encounters challenges such as inadequate infrastructure and limited access to technology, as seen at SD Inpres 4 Arborek, Raja Ampat, West Papua. To address these issues, a technology-based learning medium emphasizing Papua's biodiversity was developed. This interactive digital educational game includes features like a flora and fauna encyclopedia, quizzes, and puzzles designed to enhance students' comprehension of local natural resources. A community service activity conducted on August 21, 2024, engaged 38 students from grades 1 to 6, accompanied by two teachers and the vice principal. The activity employed direct student training and demonstrations to illustrate the game's potential as a learning tool. Students were encouraged to explore the game independently, while teachers observed its integration into daily learning routines. The results demonstrated the effectiveness of this educational medium in enhancing student motivation, engagement, and understanding. The integration of local content within the game also reinforced students' connection to their environment, cultivated cultural pride, and heightened conservation awareness. Challenges with younger students' adaptation to digital tools were mitigated through proper guidance. Questionnaire feedback indicated strong acceptance of the game as a supplementary learning resource and highlighted its potential as a model for implementing educational technology in other remote regions.